Integrating business process simulation and information system simulation for performance prediction - Heinrich, Robert; Paech, Barbara (Software and systems modeling, 2017)
Business process (BP) designs and enterprise information system (IS) designs are often not well aligned. Missing alignment may result in performance problems at run-time, such as large process execution time or overloaded IS resources. The complex interrelations between BPs and ISs are not adequately understood and considered in development so far. Simulation is a promising approach to predict performance of both BP and IS designs. Based on prediction results, design alternatives can be compared and verified against requirements. Thus, BP and IS designs can be aligned to improve performance. In current simulation approaches, BP simulation and IS simulation are not adequately integrated. This results in limited prediction accuracy due to neglected interrelations between the BP and the IS in simulation. In this paper, we present the novel approach Integrated Business IT Impact Simulation (IntBIIS) to adequately reflect the mutual impact between BPs and ISs in simulation. Three types of mutual impact between BPs and ISs in terms of performance are specified. We discuss several solution alternatives to predict the impact of a BP on the performance of ISs and vice versa. It is argued that an integrated simulation of BPs and ISs is best suited to reflect their interrelations. We propose novel concepts for continuous modeling and integrated simulation. IntBIIS is implemented by extending the Palladio tool chain with BP simulation concepts. In a real-life case study with a BP and IS from practice, we validate the feasibility of IntBIIS and discuss the practicability of the corresponding tool support.